Pemilu dan Konflik dalam Keluarga: Menjaga Harmoni dalam Perbedaan Pendapat - Moch. Azis Qoharuddin (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Conflicts within families often arise when members have different political opinions, especially during election periods. Such conflicts can threaten family harmony and disrupt relationships between family members. This study aims to explore the impact of political dissent and elections on conflict in the family as well as strategies that can be used to maintain harmony in the face of such dissent. Qualitative research was conducted using a library review approach. Data were collected through a review of libraries related to the themes of conflicts caused by elections. Data analysis was conducted through a process of reduction, presentation, and conclusion drawing. The results showed that political disagreements and elections triggered family conflicts. These conflicts include communication tensions, emotional separation, and disagreements in decision making. Factors that influence the level of conflict include the intensity of disagreement, the inability to engage in dialogue constructively, and the influence of mass media. However, this study also found strategies that can help maintain harmony in the face of political disagreements in the family. These strategies include opening a respectful dialog, willingness to listen to, trying to understand the views of the other party, and focusing on shared values and goals. In addition, the use of reliable and critical sources of information can reduce conflicts that arise.